Civil society in British history : ideas, identities, institutions - Harris, José (Oxford University Press, 2005)
This book explores the many different strands in the language of civil society from the sixteenth to the twentieth centuries. Through a series of case-studies it investigates the applicability of the term to a wide range of historical settings. The contributors show how past understandings of the term were often very different from (even in some respects the exact opposite of) those held today. - ;This book explores the many different strands in the language of civil society from the sixteenth to the twentieth centuries. Through a series of case-studies it investigates the applicability of the.